Respuesta :
Using the Pythagorean theorem:
6^2 + X^2 = 14^2
36 + x^2 = 196
X^2 = 196-36
x^2 = 160
x = SQRT(160)
x = 4 SQRT(10)
Or as a decimal:
x = 12.65 inches
6^2 + X^2 = 14^2
36 + x^2 = 196
X^2 = 196-36
x^2 = 160
x = SQRT(160)
x = 4 SQRT(10)
Or as a decimal:
x = 12.65 inches
Hey there! :)
You have to use the Pythagorean Theorem: a² + b² = c²
a² + b² = c² is the same as: c² - a² = b²
c = 14
14² = 14 × 14 = 196
a = 6
6² = 6 × 6 = 36
196 - 36 = 160
√160 = 12.65
The length of the other leg(rounded) is 12.65 in
Hope this helps :)
You have to use the Pythagorean Theorem: a² + b² = c²
a² + b² = c² is the same as: c² - a² = b²
c = 14
14² = 14 × 14 = 196
a = 6
6² = 6 × 6 = 36
196 - 36 = 160
√160 = 12.65
The length of the other leg(rounded) is 12.65 in
Hope this helps :)